Color theory - Mollica, Patti (Irvine, CA : Walter Foster, 2013)
Explores what an artist might need to know about color, including color psychology, pigment characteristics and terms, color schemes, color mixing, shadows, highlights, and more. Features step-by-step projects and practical tips and techniques to put color knowledge to effective use.
-- Introduction -- Getting started -- The history of color -- Color Basics -- Pigments & paints -- Communicating with color -- Color in action -- Closing words.
"AL53"--Cover.
Keywords: Color in art